Electrochemical Oxidation of Environmentally Persistent Perfluorooctane Sulfonate by a Novel Lead Dioxide Anode. (20th September 2016) - Zhuo, Qiongfang; Luo, Meiqing; Guo, Qingwei; Yu, Gang; Deng, Shubo; Xu, Zhencheng; Yang, Bo; Liang, Xiaoliang
Graphical abstract: Highlights: Ti/TiO2 -NTs/Ag2 O/PbO2 anode has the higher oxygen evolution potential of 2.12 V (vs. saturated calomel electrode, SCE) compared with Ti/PbO2 anode (1.33 V) and Ti/TiO2 -NTs/PbO2 (1.83 V) anode. A removal ratio of 74.87% for perfluorooctane sulfonate (PFOS) can be achieved at Ti/TiO2 -NTs/Ag2 O/PbO2 anode after 180 min of electrolysis, with a pseudo first-order kinetic constant of 0.0165 min −1 and a half-life of 43.18 min −1 . The heavy water tracer experiments show that the oxygen in the intermediate products came from electrolyte, and the intermediate products of PFOS decomposition were short-chain perfluorocarboxyl anions (i.e., C3 F7 COO −, C4 F9 COO −, C5 F11 COO −, C6 F13 COO −, and C7 F15 COO − ). Abstract: Ti/TiO2 -NTs/Ag2 O/PbO2 anode was prepared by electrodeposition technique and characterized by scanning electron microscope-energy dispersive spectrometer (SEM-EDS), X-ray diffraction (XRD), linear sweep voltammetry (LSV), and accelerated life test. Electrochemical oxidation of persistent organic pollutant wastewater perfluorooctane sulfonate (PFOS) was carried out with the novel PbO2 anode. Ti/TiO2 -NTs/Ag2 O/PbO2 anode exhibited a pyramid structure, which was the typical PbO2 electrodes prepared using electrochemical deposition method. XRD spectra indicated that diffraction peaks of PbO2 coating conformed to that of JCPDS (Joint Committee on Powder Diffraction Standards) card for β-PbO2 . Ti/TiO2 -NTs/Ag2 O/PbO2 anode showed high oxygen evolution potential, and longer life service, compared with Ti/PbO2 and Ti/TiO2 -NTs/PbO2 anodes. The degradation ratio of PFOS (90 mL of 0.0929 mmol L −1 ) was 74.87%, with a pseudo first-order kinetic constant of 0.0165 min −1 and a half-life of 43.18 min −1 at a constant current density of 30 mA cm −2 after 180 min of electrolysis. PFOS oxidation yielded sulfate, fluoride, and perfluorocarboxyl anions (i.e., C3 F7 COO −, C4 F9 COO −, C5 F11 COO −, C6 F13 COO −, and C7 F15 COO − ). The electrospray ionization (ESI) mass spectrum confirmed that oxygen in the intermediate products originated from a heavy-oxygen water electrolyte, and the degradation of PFOS was initiated by the dissociation of a sulfonic group. A possible mechanism was revealed; that was, PFOS was desulfated at the anode to form C8 F17 · and then transformed into C8 F17 OH, followed by intramolecular rearrangement and hydrolysis reactions to form C7 F15 COO − . Kolbe decarboxylation occurred in C7 F15 COO − at the anode to generate C7 F15 ·, which evolved into C6 F13 COO − in a similar way and the CF2 unit fell off from C7 F15 COO − . PFOS was gradually degraded into short-chain perfluorocarboxyl anions by repeating the CF2 unzipping cycle.